Heritability of the rate of torque development - Lykoudi, T. K.; Athanasopoulos, S. I.; Geladas, N. D.; Katopi, D. K.; Klissouras, V. (The Journal of Sports Medicine and Physical Fitness, 2016)
AIM: The aim of this study was to estimate the genetic and environmental contribution to the variation observed in the rate of torque development (RTD), which is considered an important determinant of sport performance.